Haptoglobin phenotype and intensive glycemic control for coronary artery disease risk reduction in people with type two diabetes: The Veterans Affairs Diabetes Trial - Leah E Cahill; Rachel A Warren; Gideon D Bahn; Allie S Carew; Andrew P Levy; John Sapp; Eric B Rimm; Peter Reaven (Elsevier, 2024)
Background: Intensive glycemic control reduced the risk of coronary artery disease (CAD) events among White ACCORD study participants with the haptoglobin (Hp)2-2 phenotype, and not among participants without the Hp2-2 phenotype. It is unknown whether these results persist in a population with more severe diabetes. Methods: Haptoglobin phenotype was measured in 1746 (97 %) samples from the Veterans Affairs Diabetes Trial (VADT) randomized controlled trial. Multivariable-adjusted Cox regression models assessed the effect of intensive therapy on CAD risk among participants with and without the Hp2-2 phenotype separately and when stratified within pre-specified race/ethnicity-based subgroups. Time-varying (achieved) HbA1c data (<7.0 % or ≥8.0 % compared to 7.0-7.9, updated every 3 months) were also analyzed in relation to CAD risk within each phenotype. Results: 567 (32.5 %) participants had the Hp2-2 phenotype. Compared to standard therapy, intensive glycemic control was not associated with risk of CAD among participants with the non-Hp2-2 or the Hp2-2 phenotype or for any race/ethnicity-based group. Compared to HbA1c of 7.0-7.9 %, having HbA1c <7.0 % was not associated with CAD risk for either phenotype or among any race/ethnicity-based group. Having HbA1c ≥8.0 % was associated with an increased risk of CAD among Hispanic participants without the Hp2-2 phenotype (HR= 3.61, 95 % CI: 1.54-8.41, p-interaction=0.53). Conclusion: The effect of intensive glycemic therapy on CAD events was not dependent on Hp phenotype in the VADT study of veterans with severe diabetes who may represent a population where Hp phenotype information would not be useful for personalizing diabetes management. However, further research is needed to determine if these results are conclusive.